Methemoglobinemia Associated with Late-Onset Neonatal Sepsis: A Single-Center Experience - Schierz, Ingrid Anne Mandy; Pinello, Giuseppa; Piro, Ettore; Giuffrè, Mario; Corsello, Giovanni (American Journal of Perinatology, 2019)
Objective Methemoglobinemia (MetHb) is a rare congenital or acquired cause of infantile cyanosis. We examined the role of MetHb in a neonatal intensive care unit (NICU).Study Design A retrospective observational study was conducted reviewing blood gas analyses of hospitalized newborns over a 2-year period. MetHb-positive patients (MetHb >1.8%) were matched with a control group for gestational age, weight, disease, and illness severity at admission. Maternal, neonatal, clinical, and laboratory parameters were collected and analyzed in both groups.Results MetHb incidence was 6%. The mean MetHb in the case group was 7.2%, and the first positive samples were observed at a mean of 22 days of life, 6 days prior to clinical or culture-proven sepsis. We identified low maternal age (31 vs. 34 years; p = 0.038), sepsis (90 vs. 45%; p = 0.022), and protracted parenteral nutrition (46 vs. 23 days; p = 0.013) as risk factors for MetHb, and early minimal enteral feeding as protective factor (12th vs. 9th day; p = 0.038).Conclusion MetHb has a high occurrence in NICU and can be a helpful prognostic indicator of an infectious process. Understanding and prompt identification of MetHb can allow pediatricians to implement a life-saving therapy.
Keywords: observational study; cyanosis; anemia; hypoxia; newborn